Sealing Efficacy of Single-cone Obturation Technique with MTA and CEM Cement: An in Vitro Bacterial Leakage Study - Mohammad Samiei; Mohammad Aghazadeh; Farrokh Farhadi; Naeimeh Shahvegha; Ali Torab; Seyyed Mahdi Vahid Pakdel (Tabriz University of Medical Sciences, 2014)
Background and aims. Various materials and methods have been introduced for obturating cleaned and shaped root canal systems. This in vitro study aimed to evaluate the sealing ability of single-cone obturation technique with mineral trioxide aggregate and calcium-enriched mixture based on bacterial leakage approach. Materials and methods. Sixty-four single-canal teeth were prepared and randomly divided into 5 groups, consisting of three experimental groups (n = 16) and two control groups (n = 8). In group 1, root canal obturation was performed using gutta-percha with 0.02 taper and AH26 sealer by lateral compaction technique. In groups 2 and 3, single Protaper guttapercha cone was used for obturation with MTA and CEM cement, respectively. A bacterial leakage apparatus was utilized for leakage assessment for 60 days. Leakage comparison between the experimental groups was performed by one-way ANOVA using SPSS 16 statistical software. Results. The mean bacterial leakage intervals in groups 1, 2 and 3 were 33.68 ± 9.39, 40.68 ± 11.03 and 39.56 ± 9.03 days, respectively. One-way ANOVA indicated no significant differences in bacterial leakage between the three experimental groups (P = 0.109). Conclusion. Single-cone obturation with well-fitted gutta-percha and MTA and CEM cement is an appropriate alternative for traditional lateral compaction technique.